Impact of storm propagation speed on coastal flood hazard induced by offshore storms in the North Sea. (November 2019) - Wei, Xiaoyan; Brown, Jennifer M.; Williams, Joanne; Thorne, Peter D.; Williams, Megan E.; Amoudry, Laurent O.
Abstract: Storm propagation speed (SPS) can noticeably impact coastal floods around semi-closed basins influenced by extratropical offshore storms. As a case study, the SPS impact on potential flood hazards due to extreme water levels along the UK east coast was studied using a numerical shelf sea model (FVCOM). The storm Xaver, which caused the largest North Sea surge over the past 60 years, was studied as a base scenario. Halving/doubling the SPS results in a smaller surge and a longer/shorter surge duration. Hence, the largest peak water level was found at actual speed, while the largest potential flood hazard occurred at half speed. Tide–surge interaction tends to reduce the M2 tide along the coast and advance its propagation for all SPS. A three-dimensional semi-analytical model, including a time-periodic wind forcing, was used to investigate the dominant mechanisms behind the surge dynamics, where wind duration is directly related to the SPS. Long wind durations correspond to small SPS, and vice versa. The semi-analytical model was applied to the North Sea. The model reproduces the spatial features of the North Sea surge and its dependence on SPS, confirming the surge induced by offshore storms is primarily associated with wind set-up. Model results suggest the SPS of Xaver is likely to have contributed greatly to the occurrence of the largest North Sea surge due to wind-generated resonance. The impact of the SPS on the surge and tide–surge interaction are of great importance to coastal flood hazard assessment. Highlights: Fast moving storms can cause large coastal floods due to basin resonance. The propagation speed of the storm Xaver is responsible for its coastal impact. Surge can advance the tidal propagation, which is more evident for slower storms.